A DESCRIPTIVE STUDY ON JUNIOR HIGH SCHOOL STUDENTS’ ANXIETY FACTORS IN READING - Rani Humairoh; Yanti Sri Rezeki; Urai Salam (STKIP PGRI Jombang, 2023)
This study aimed to analyze the factors that cause anxiety in reading based on the FLRAS by Saito, Garza, and Horwitz (1999) and the students’ ways to overcome anxiety. The subjects of this study were 33 ninth-grade students of SMP Negeri 4 Sungai Raya. This study used a descriptive study and data collected from the provision of questionnaires, namely a close-ended questionnaire and an open-ended questionnaire. The results explained the factors of anxiety in reading and how to overcome the anxiety in reading. The factors included worrying about reading effects, afraid of making errors, unfamiliar culture, unfamiliar topics, and unknown vocabulary. The efforts that the students used to overcome their anxiety in reading were preparation, relaxation, positive thinking, peer-seeking, and resignation.